1989
DOI: 10.1182/blood.v73.1.57.bloodjournal73157
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of acute lymphoblastic leukemia in adults with intensive induction, consolidation, and maintenance chemotherapy

Abstract: The Southwest Oncology Group conducted a study of acute lymphoblastic leukemia (ALL) in adults over a 5-year period, testing the utility of the L-10M regimen initially described by the group from Memorial Sloan- Kettering Cancer Center. One hundred sixty-eight eligible patients were treated with this intensive combination chemotherapy regimen. One hundred fifteen (68%) achieved complete remission. With the current median follow-up time of 34.5 months, the median durations of remission, relapse-free survival, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
21
0
6

Year Published

1995
1995
2012
2012

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 60 publications
(29 citation statements)
references
References 22 publications
2
21
0
6
Order By: Relevance
“…The mild induction therapy employed in this trial induced a 79 . 3% CR rate, comparable to the rate recorded both in single or multi-institutional trials, which employed either more intensive conventional induction schedules or unconventional ones (Lister et al, 1978;Fiere et al, 1987;Hoelzer et al, 1989;Hussein et al, 1989;Clarkson et al, 1990;Fiere et al, 1993;Durrant & Richard, 1993;Weiss et al, 1993;Evensen et al, 1994). The second aim of our trial was to evaluate the impact of an early intensive consolidation phase on CR length.…”
Section: Discussionsupporting
confidence: 70%
See 1 more Smart Citation
“…The mild induction therapy employed in this trial induced a 79 . 3% CR rate, comparable to the rate recorded both in single or multi-institutional trials, which employed either more intensive conventional induction schedules or unconventional ones (Lister et al, 1978;Fiere et al, 1987;Hoelzer et al, 1989;Hussein et al, 1989;Clarkson et al, 1990;Fiere et al, 1993;Durrant & Richard, 1993;Weiss et al, 1993;Evensen et al, 1994). The second aim of our trial was to evaluate the impact of an early intensive consolidation phase on CR length.…”
Section: Discussionsupporting
confidence: 70%
“…The proposal that adult ALL can be cured through chemotherapy only is becoming a reality. The various therapeutic strategies employed in the past decade enabled 25-35% of these patients to become long-term survivors and possibly to be cured (Schauer et al, 1983;Omura & Raney, 1985;Hoelzer et al, 1989;Hussein et al, 1989;Clarkson et al, 1990;Preti & Kantarjian, 1994). The improvement in the percentage of long-term survivors is often achieved by intensifying the therapeutic regimens, the toxicity of which is not negligible.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, this trial is without an upper age limit; thus the patient population has a relatively high median age (42 years). Age is recognized by many authors as one of the most important prognostic factors both for CR rate and outcome (Hoelzer et al , 1988; Hussein et al , 1989; Kantarjian et al , 1994; Larson et al , 1995). Our study showed an estimated 3 year CCR of 36% and 5 year CCR of 30%, with better results for pre‐B ALL compared with T‐ALL.…”
Section: Discussionmentioning
confidence: 99%
“…Treatment results in elderly ALL patients are worse than those observed in younger adults [14,31]. Older age is predictive of shorter remission duration and survival in most adult ALL studies [31][32][33][34][35]. Several factors may account for this, such as an increased toxicity of therapy results with higher morbidity and mortality during induction therapy or an incomplete drug administration and extended intervals between cycles leading to inferior long-term results.…”
Section: Discussionmentioning
confidence: 99%